(The impact of oil price shocks on the performance of the Saudi financial market (2003- 2016 - Ahmed, Mohammed Faisal Hassan Mohammed (Journal of Economic, Administrative and Legal Sciences, 2019)
This study sought to analyze the impact of oil price fluctuations on the performance of the Saudi Stock Exchange by analyzing the impact of oil price fluctuations on the volume of trading, the market index and the prices of shares of listed companies in the market. The study used the inductive method to derive hypotheses, and the method of quantitative analysis to test the validity of these hypotheses. The study found that the fluctuations in oil prices do not explain the variation in the performance of the financial market (volume and market index) or the performance of companies listed in the Saudi Stock Exchange (stock prices). The study explained this result in the light of investor interest in other factors such as the financial performance of companies, the results of companies’ business, dividends and others, and ignoring the impact of oil price fluctuations. The study recommended testing the relationship between the performance of the financial market and the factors influencing it such as dividends, market values ​​of stocks and other factors.